3x+9=4-2x

Simple and best practice solution for 3x+9=4-2x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+9=4-2x equation:


Simplifying
3x + 9 = 4 + -2x

Reorder the terms:
9 + 3x = 4 + -2x

Solving
9 + 3x = 4 + -2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2x' to each side of the equation.
9 + 3x + 2x = 4 + -2x + 2x

Combine like terms: 3x + 2x = 5x
9 + 5x = 4 + -2x + 2x

Combine like terms: -2x + 2x = 0
9 + 5x = 4 + 0
9 + 5x = 4

Add '-9' to each side of the equation.
9 + -9 + 5x = 4 + -9

Combine like terms: 9 + -9 = 0
0 + 5x = 4 + -9
5x = 4 + -9

Combine like terms: 4 + -9 = -5
5x = -5

Divide each side by '5'.
x = -1

Simplifying
x = -1

See similar equations:

| x-3x+7=13 | | x+24=16*24 | | 7f+5=58 | | 8h+6=2(3h-9) | | (8t^2-t-7)*(8t^2+8t-1)= | | -8+4=12 | | 1010x-3(x-6)=x+30 | | 1/3x^2-1/2x=1 | | 449=8x+273 | | (-8)=12 | | 2x^3-7x^2+4x= | | 3x+7=11-x | | x^2*x^2=102 | | 7(6x-1)-5(12x-7)=23-3(2x+1) | | 6x-8=4(-2+5) | | 6x^3-17x^2+6x+8= | | 120-2x=16x+20 | | 700=3(27f+5) | | (5x-2)*(x^2-4x+4)= | | 78/5=x/8 | | 10w^2+31w-14=0 | | 10-7x=39-14x | | x(-8)=12 | | 4x^2-36=3x^2-5x | | 2x+3=3x-10-3(9x-6) | | g(x)=X^2-15x+24 | | 18.71m+15.23m=x | | -0.2x=4 | | x^4-18x^2+27=0 | | 2x-5+2x-5=2x | | 1*x=54/5 | | 3/5*(9) |

Equations solver categories